Searches for the baryon- and lepton-number violating decays B0→Λ+cl−, B−→Λl−, and B−→Λl[bar]− - Amo Sanchez, Pablo del; Marks, Jörg; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2011)
Searches for B mesons decaying to final states containing a baryon and a lepton are performed, where the baryon is either Λc or Λ and the lepton is a muon or an electron. These decays violate both baryon and lepton number and would be a signature of physics beyond the standard model. No significant signal is observed in any of the decay modes, and upper limits in the range (3.2-520)×10−8 are set on the branching fractions at the 90% confidence level.
Im Titel ist die Zahl 0, das Pluszeichen und das Minuszeichen hochgestellt
Im Titel ist der Buchstabe c tiefgestellt
Im Titel steht der Ausdruck "Λl" mit einem Oberstrich
*BABAR Collaboration: P. del Amo Sanchez, J. Marks, U. Uwer [und 428 weitere Personen]
Gesehen am 04.10.2022